Family financial well-being of selected Filipino families involved in multilevel marketing in Metro Manila - Purugganan, Marvin B.; Chua, Consuelo Trio (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
The study aims to explore the financial wellbeing FWB of selected Multilevel Marketing MLM members and their families. Specifically, the study aims to describe the family financial wellbeing of MLM members determine MLM factors that contribute to their family financial wellbeing and determine the contribution of family members to the successful operations of the MLM business. The study used a mixed method design, which employed both the quantitative and qualitative data to determine the connection between family financial wellbeing and MLM factors and the contribution of family members to the successful MLM business operations. A modified FWB scale was administered to determine the family FWB of the respondents while indepth one interview was used to determine the contribution of family members to the MLM business. The family FWB scores of the respondents show that income is a major factor influencing the families FWB. However, closer analysis of the scores shows that there are other factors which also affect FWB. MLM factors that contribute to FWB include potential for higher earnings, opportunity to enjoy earnings, and MLM as a viable business opportunity among others. On the other hand, family members contribute to the successful operations of the MLM through various support mechanisms including network genealogy management, direct selling, business presentations and training, product testing and testimony, online promotion, emotional support, and product management and delivery. The study recommends a parallel study that looks into families who are unsuccessful in MLM.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Families -- Philippines -- Economic aspects; Finance, Personal -- Philippines